Andesite Quality based on Compressive Strength Tests in the Ulujadi area, Palu City and the Banawa Area, Donggala Regency - Alimuddin, Fauziah; Jaya, Asri; Sirajuddin, Haerany (Departemen Geofisika, FMIPA - Universitas Hasanuddin, Makassar, 2024)
The research location is located in the Ulujadi area, Palu City, Central Sulawesi Province, which is one of the areas that has abundant andesite mineral content. This research aims to optimizing use of andesite rocks in the Ulujadi area of ​​Palu City. The research was carried out using qualitative and quantitative methods in the form of rock sampling and laboratory analysis, namely compressive strength test analysis to determine the technical properties of rocks and petrographic analysis to determine the quality of andesite based on the minerals that make up it. The results of petrographic analysis show that the andesite rocks in the study area are composed of minerals that have a good level of resistance. ST 07 has a mineral composition of plagioclase (38%), pyroxene (5%), biotite (5%), hornblende (7%), and soil mass (45%), and has a compressive strength test of 123 MPa, included in the classification strong, and is used as a foundation for light to medium buildings (SNI 03-0394-1989). ST 08 has a mineral composition of plagioclase (32%), ground mass (50%), opaque minerals (5%), orthoclase (5%), quartz (4%), and hornblende (4%), with a compressive strength test value of 97MPa, including in the strong classification, and can be used as a foundation for light to medium buildings. Meanwhile, ST 09 has a mineral composition of plagioclase (30%), hornblende (12%), quartz (3%), biotite (3%), orthoclase (7%), pyroxene (5%), and soil mass (40%). ), it is included in the weak category due to the relatively high degree of weathering, and can only be used as an ornamental stone.